PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TGT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX MTsN TARUSAN TAHUN PELAJARAN 2013/2014 - listiawati, Rosi; mukhni, mukhni; Haryono, Yulia (STKIP PGRI Sumbar, 2014)
ABSTRACTThe background reason of this research is the understanding of mathematical concept that still low and the students are still irresponsible for the assignment given by the teacher. The aim of this research is to know whether the understanding of the mathematical concept of the student will be better if cooperative learning method TGT is applied rather than Â the conventional way to the 9th grade students of MTsN Tarusan School year 2013/2014. The type of this research is experimental research, with random research design to subject. The instrument used for this research is the mathematical concept quiz and test. Based on the test result, its shown that one of the sample class is not normally distributed. Data analysis was done by using Mann-U Whitney test with the help of minitab. The result of the hypothesis test is p-value=0.0073. it is seen that the p-value < Î±, then the hypothesis of the research is acceptable. So it is concluded that the understanding of the mathematical concept of the student will be better by using the cooperative learning method TGT rather than the conventional way of 9th grade students of MTsN Tarusan.